theorem lmemnth (a l: nat) {n: nat}: $ a IN l <-> E. n nth n l = suc a $;
Step | Hyp | Ref | Expression |
---|---|---|---|
1 |
_1 = l -> a = a |
||
2 |
_1 = l -> _1 = l |
||
3 |
_1 = l -> (a IN _1 <-> a IN l) |
||
4 |
_1 = l -> n = n |
||
5 |
_1 = l -> nth n _1 = nth n l |
||
6 |
_1 = l -> suc a = suc a |
||
7 |
_1 = l -> (nth n _1 = suc a <-> nth n l = suc a) |
||
8 |
_1 = l -> (E. n nth n _1 = suc a <-> E. n nth n l = suc a) |
||
9 |
_1 = l -> (a IN _1 <-> E. n nth n _1 = suc a <-> (a IN l <-> E. n nth n l = suc a)) |
||
10 |
_1 = 0 -> a = a |
||
11 |
_1 = 0 -> _1 = 0 |
||
12 |
_1 = 0 -> (a IN _1 <-> a IN 0) |
||
13 |
_1 = 0 -> n = n |
||
14 |
_1 = 0 -> nth n _1 = nth n 0 |
||
15 |
_1 = 0 -> suc a = suc a |
||
16 |
_1 = 0 -> (nth n _1 = suc a <-> nth n 0 = suc a) |
||
17 |
_1 = 0 -> (E. n nth n _1 = suc a <-> E. n nth n 0 = suc a) |
||
18 |
_1 = 0 -> (a IN _1 <-> E. n nth n _1 = suc a <-> (a IN 0 <-> E. n nth n 0 = suc a)) |
||
19 |
_1 = a2 -> a = a |
||
20 |
_1 = a2 -> _1 = a2 |
||
21 |
_1 = a2 -> (a IN _1 <-> a IN a2) |
||
22 |
_1 = a2 -> n = n |
||
23 |
_1 = a2 -> nth n _1 = nth n a2 |
||
24 |
_1 = a2 -> suc a = suc a |
||
25 |
_1 = a2 -> (nth n _1 = suc a <-> nth n a2 = suc a) |
||
26 |
_1 = a2 -> (E. n nth n _1 = suc a <-> E. n nth n a2 = suc a) |
||
27 |
_1 = a2 -> (a IN _1 <-> E. n nth n _1 = suc a <-> (a IN a2 <-> E. n nth n a2 = suc a)) |
||
28 |
_1 = a1 : a2 -> a = a |
||
29 |
_1 = a1 : a2 -> _1 = a1 : a2 |
||
30 |
_1 = a1 : a2 -> (a IN _1 <-> a IN a1 : a2) |
||
31 |
_1 = a1 : a2 -> n = n |
||
32 |
_1 = a1 : a2 -> nth n _1 = nth n (a1 : a2) |
||
33 |
_1 = a1 : a2 -> suc a = suc a |
||
34 |
_1 = a1 : a2 -> (nth n _1 = suc a <-> nth n (a1 : a2) = suc a) |
||
35 |
_1 = a1 : a2 -> (E. n nth n _1 = suc a <-> E. n nth n (a1 : a2) = suc a) |
||
36 |
_1 = a1 : a2 -> (a IN _1 <-> E. n nth n _1 = suc a <-> (a IN a1 : a2 <-> E. n nth n (a1 : a2) = suc a)) |
||
38 |
~a IN 0 |
||
40 |
suc a != nth n 0 -> nth n 0 != suc a |
||
41 |
conv ne |
suc a != nth n 0 -> ~nth n 0 = suc a |
|
43 |
nth n 0 = 0 |
||
44 |
suc a != nth n 0 <-> suc a != 0 |
||
45 |
suc a != 0 |
||
46 |
suc a != nth n 0 |
||
47 |
~nth n 0 = suc a |
||
48 |
~E. n nth n 0 = suc a |
||
49 |
a IN 0 <-> E. n nth n 0 = suc a |
||
50 |
a IN a1 : a2 <-> a = a1 \/ a IN a2 |
||
52 |
E. n (n = 0 /\ nth n (a1 : a2) = suc a \/ ~n = 0 /\ nth n (a1 : a2) = suc a) <-> E. n (n = 0 /\ nth n (a1 : a2) = suc a) \/ E. n (~n = 0 /\ nth n (a1 : a2) = suc a) |
||
55 |
(n = 0 \/ ~n = 0) /\ nth n (a1 : a2) = suc a <-> n = 0 /\ nth n (a1 : a2) = suc a \/ ~n = 0 /\ nth n (a1 : a2) = suc a |
||
58 |
n = 0 \/ ~n = 0 |
||
59 |
(n = 0 \/ ~n = 0) /\ nth n (a1 : a2) = suc a <-> nth n (a1 : a2) = suc a |
||
60 |
n = 0 /\ nth n (a1 : a2) = suc a \/ ~n = 0 /\ nth n (a1 : a2) = suc a <-> nth n (a1 : a2) = suc a |
||
61 |
E. n (n = 0 /\ nth n (a1 : a2) = suc a \/ ~n = 0 /\ nth n (a1 : a2) = suc a) <-> E. n nth n (a1 : a2) = suc a |
||
62 |
E. n (n = 0 /\ nth n (a1 : a2) = suc a) \/ E. n (~n = 0 /\ nth n (a1 : a2) = suc a) <-> E. n nth n (a1 : a2) = suc a |
||
64 |
a1 = a <-> a = a1 |
||
65 |
suc a1 = suc a <-> a1 = a |
||
66 |
nth 0 (a1 : a2) = suc a1 |
||
67 |
n = 0 -> nth n (a1 : a2) = nth 0 (a1 : a2) |
||
68 |
n = 0 -> nth n (a1 : a2) = suc a1 |
||
69 |
n = 0 -> (nth n (a1 : a2) = suc a <-> suc a1 = suc a) |
||
70 |
n = 0 -> (nth n (a1 : a2) = suc a <-> a1 = a) |
||
71 |
n = 0 -> (nth n (a1 : a2) = suc a <-> a = a1) |
||
72 |
E. n (n = 0 /\ nth n (a1 : a2) = suc a) <-> a = a1 |
||
73 |
a = a1 <-> E. n (n = 0 /\ nth n (a1 : a2) = suc a) |
||
74 |
(a IN a2 <-> E. n nth n a2 = suc a) -> (a = a1 <-> E. n (n = 0 /\ nth n (a1 : a2) = suc a)) |
||
78 |
n = a3 -> nth n a2 = nth a3 a2 |
||
79 |
n = a3 -> (nth n a2 = suc a <-> nth a3 a2 = suc a) |
||
80 |
E. n nth n a2 = suc a <-> E. a3 nth a3 a2 = suc a |
||
83 |
n != 0 <-> E. a3 n = suc a3 |
||
84 |
conv ne |
~n = 0 <-> E. a3 n = suc a3 |
|
85 |
nth n (a1 : a2) = suc a -> (~n = 0 <-> E. a3 n = suc a3) |
||
86 |
~n = 0 /\ nth n (a1 : a2) = suc a <-> E. a3 (n = suc a3 /\ nth n (a1 : a2) = suc a) |
||
87 |
E. n (~n = 0 /\ nth n (a1 : a2) = suc a) <-> E. a3 E. n (n = suc a3 /\ nth n (a1 : a2) = suc a) |
||
89 |
nth (suc a3) (a1 : a2) = nth a3 a2 |
||
90 |
n = suc a3 -> nth n (a1 : a2) = nth (suc a3) (a1 : a2) |
||
91 |
n = suc a3 -> nth n (a1 : a2) = nth a3 a2 |
||
92 |
n = suc a3 -> (nth n (a1 : a2) = suc a <-> nth a3 a2 = suc a) |
||
93 |
E. n (n = suc a3 /\ nth n (a1 : a2) = suc a) <-> nth a3 a2 = suc a |
||
94 |
E. a3 E. n (n = suc a3 /\ nth n (a1 : a2) = suc a) <-> E. a3 nth a3 a2 = suc a |
||
95 |
bitr* |
E. n (~n = 0 /\ nth n (a1 : a2) = suc a) <-> E. a3 nth a3 a2 = suc a |
|
96 |
E. n nth n a2 = suc a <-> E. n (~n = 0 /\ nth n (a1 : a2) = suc a) |
||
97 |
a IN a2 <-> E. n nth n a2 = suc a <-> (a IN a2 <-> E. n (~n = 0 /\ nth n (a1 : a2) = suc a)) |
||
98 |
bi1* |
(a IN a2 <-> E. n nth n a2 = suc a) -> (a IN a2 <-> E. n (~n = 0 /\ nth n (a1 : a2) = suc a)) |
|
99 |
(a IN a2 <-> E. n nth n a2 = suc a) -> (a = a1 \/ a IN a2 <-> E. n (n = 0 /\ nth n (a1 : a2) = suc a) \/ E. n (~n = 0 /\ nth n (a1 : a2) = suc a)) |
||
100 |
(a IN a2 <-> E. n nth n a2 = suc a) -> (a = a1 \/ a IN a2 <-> E. n nth n (a1 : a2) = suc a) |
||
101 |
(a IN a2 <-> E. n nth n a2 = suc a) -> (a IN a1 : a2 <-> E. n nth n (a1 : a2) = suc a) |
||
102 |
a IN l <-> E. n nth n l = suc a |